Flight : Projects. Quizzes. Fun Facts. Cartoon - Becklake, Sue (San Diego : Silver Dolphin Books, 2008)
These 100 facts about flight are accompanied by detailed photographs to challenge children, acting as an incentive as they make their way through the book. Projects to make and do, amazing facts and cartoons add an extra element of fun.
Keywords: Airplanes -- Aviation